2019
DOI: 10.1098/rsos.190965
|View full text |Cite
|
Sign up to set email alerts
|

Old lake versus young taxa: a comparative phylogeographic perspective on the evolution of Caspian Sea gastropods (Neritidae: Theodoxus )

Abstract: The Caspian Sea has been a highly dynamic environment throughout the Quaternary and witnessed major oscillations in lake level, which were associated with changes in salinity and habitat availability. Such environmental pressures are considered to drive strong phylogeographic structures in species by forcing populations into suitable refugia. However, little is actually known on the effect of lake-level fluctuations in the Caspian Sea on its aquatic biota. We compared the phylogeographic patterns of the aquati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 68 publications
6
32
0
Order By: Relevance
“…Previously published phylogenetic relationships among species of Theodoxus are spread between a number of different studies (e.g. Bunje and Lindberg 2007;Sands et al 2019aSands et al , 2019b. These phylogenies still lack some commonly recognised morphospecies.…”
Section: Phylogenetics and Species Delimitationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously published phylogenetic relationships among species of Theodoxus are spread between a number of different studies (e.g. Bunje and Lindberg 2007;Sands et al 2019aSands et al , 2019b. These phylogenies still lack some commonly recognised morphospecies.…”
Section: Phylogenetics and Species Delimitationmentioning
confidence: 99%
“…To consolidate and expand upon recommendations from these studies, we constructed a new, robust and time-calibrated Bayesian phylogeny. We supplemented data from published studies available on GenBank (Bunje and Lindberg 2007;Fehér et al 2012;Sands et al 2019aSands et al , 2019b with new data produced herein to incorporate as many morphospecies and Asian localities as possible to allow for sound taxonomic inferences and distribution assessments (Suppl material 1: Table S1). Moreover, Sands et al (2019a) identified three new species, which we describe herein.…”
Section: Phylogenetics and Species Delimitationmentioning
confidence: 99%
See 3 more Smart Citations